On Taboos - Continisio, Tommaso; Sebellin, Rossana (Linguæ & - Journal of Modern Languages and Cultures, 2024)
By common understanding, taboos demarcate the forbidden, the impure, or the sacred, drawing a line between what is allowed and what is not. However, despite their apparent universality across cultures, time periods, and belief systems, taboos in fact prove far more elusive and contradictory than they first appear, resisting any fixed definition.